Early school dropout in distance higher education: An analysis according to data from the degree in letters course at IFPB (Research, Society and Development, 2021)
Early School Evasion in an undergraduate course in distance education is a peculiarity of the type of dropout that is intrinsically related to the moment when this student leaves the educational unit. There is little material in the scientific literature to discuss this academic phenomenon and a real solution to the problem. Methodologically, we adopted the assumptions of a quali / quanti approach, configuring an applied nature research with an explanatory objective. With data collection procedures carried out via bibliographic, documentary and case study research. We analyzed the distance learning degree course at the IFPB with incoming students in the first semester of the 2019 academic year. Defining retention policies, analyzing the individual probabilities of dropping out since the student's admission and redefining pedagogical practices are notes that can direct the actors educational institutions to establish conducts that reverberate in the permanence of this student in school.